Effects of specific muscle imbalance improvement training on the balance ability in elite fencers - Kim, T. W.; Kil, S. K.; Chung, J. W.; Park, J. C.; Oh, E. Y.; Kong, S. J.; Moon, J. H. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to investigate the effects of specific muscle imbalance improvement training (SMIIT) on the balance ability. Subjects were 9 male national team fencers with 28.2±2.2 yrs, 182.3±4.0 cm, and 76.5±8.2 kg. The SMIIT included flexibility training, Pilates, muscle balance training and was conducted for 12 weeks with 4 times per week. As a result, there was no significant difference in COM dispersion among static balance maintaining abilities, but reduction in the COP dispersion was shown. In conclusion, SMIIT seemed to affect in improving dynamic balance maintaining abilities especially in non-dominant leg.